Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1023/a:1026390117562
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Local application of serotonin (5-hydroxytryptamine, 5-HT) to the soma of command neurons LPa2, LPa3, PPa3, and PPa2 of edible snail Helix lucorum reversibly decreased acetylcholine-induced inward current in these neurons. NAN-190 and methiothepin, antagonists of 5-HT1 serotonin receptors, prevented this modulatory effect of 5-HT. By contrast, LY-53.857, ICS-205.930, and SDZ-205.557, antagonists of 5-HT2, 5-HT3, and 5-HT4 serotonin receptors, respectively, produced no effect on the modulatory effect of seroton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…These results correlate with the data of Glanzman et al ( 1989 ) which show the inhibition of the heterosynaptic facilitation in Aplysia by the neurotoxin 5,7-DHT. Data from the literature (Pivovarov and Nistratova, 2003 ; Abramova et al, 2005 ) and our results show that premotor interneurons respond to 5-HT, i.e., 5-HT may modulate the behavioral effects. Direct evidence of the possibility of electrophysiological modulatory effects of the serotonergic neuron Pd4 on the premotor interneuron LPa3 was found by Balaban et al ( 2001 ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…These results correlate with the data of Glanzman et al ( 1989 ) which show the inhibition of the heterosynaptic facilitation in Aplysia by the neurotoxin 5,7-DHT. Data from the literature (Pivovarov and Nistratova, 2003 ; Abramova et al, 2005 ) and our results show that premotor interneurons respond to 5-HT, i.e., 5-HT may modulate the behavioral effects. Direct evidence of the possibility of electrophysiological modulatory effects of the serotonergic neuron Pd4 on the premotor interneuron LPa3 was found by Balaban et al ( 2001 ).…”
Section: Discussionsupporting
confidence: 75%
“…For example, the facilitation action on reflex activity and on central pattern generators (Gillette, 2006 ). The increase in excitability of neurons under the action of 5-HT has been noted by a number of authors (Frysztak and Crow, 1997 ; Liao et al, 1999 ; Balaban et al, 2001 ; Pivovarov and Nistratova, 2003 ; Abramova et al, 2005 ; Dumitriu et al, 2006 ; Hawkins et al, 2006 ). Jin and co-authors have shown that 5-HT increases the peak amplitude of the complex excitatory post-synaptic potential induced by light, and also increases the internal excitability and the spike activity of type Ie(A) interneurons of the mollusk Hermissenda (Jin et al, 2009 ).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It was also shown that antagonist of 5-HT receptors mianserin blocked two forms of withdrawal behavior of Lymnaea caused by an unconditioned stimulus (extract of crayfish tissue), and another 5-HT receptor antagonist methylsergide blocked formation of the long-term memory after training (Il-Han et al, 2010 ). The 5-HT 1 receptors were described for the soma of identified premotor interneurons of the terrestrial snail, which are the object of our study (Pivovarov and Nistratova, 2003 ; Abramova et al, 2006 ).…”
Section: Introductionmentioning
confidence: 92%